Aparthaids: uma análise sociológica da manipulação e ocultação do estigma da AIDS - Leite, Kelma Lima Cardoso (2006)
This dissertation highlights an analysis of motivations involved in the manipulation and hiding of HIV/AIDS found between asymptomatic seropositive patients that present a medical follow-up as conducted by the Sao Jose Hospital. Considering theoretical findings about health, disease, sex, sexuality, physical and social death, rejection, stigma and morals, it was possible to understand about what is lying under the fear of having the same positive serological condition for the aids presented by relatives, neighbors or friends. The findings from interviews with six women and four men who participate in the research show that that they are afraid not only of rejection and social death, but also the syndrome of “culpability” and the accusation deriving from the representation that links aids to possible promiscuous behavior.